PENGARUH CUSTOMER RELATIONSHIP, STRATEGIC SUPPLIER, INFORMATION SHARING & POSTPONEMENT TERHADAP ORGANIZATIONAL PERFORMANCE YANG DIMEDIASI INBOUND DAN OUTBOUND INNOVATION - Haryanto, Tandri; Arianto, Radityo Fajar (Transpublika Publisher, 2024)
Technological advancements and the growth of e-commerce have increased the complexity of supply chain management, making it more vulnerable to disruptions. The COVID-19 pandemic has highlighted this vulnerability, leading organizations to reassess traditional risk management approaches and emphasize collaborative partnerships to enhance supply chain value. This study aims to evaluate the impact of Customer Relationship (CR), Quality of Information Sharing (QIS), Strategic Supplier Partnership (SSP), Postponement (P), Top Management Knowledge Value (TMKV), and Knowledge Sharing Practice (KSP) on Organizational Performance (OP), with Inbound and Outbound Open Innovation (IOI and OOI) as mediating variables. Data was collected from 164 professionals in Jakarta using the Purposive Sampling method through online questionnaires on Google Forms. Data analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results of the study show that all independent variables positively affect organizational performance, although not all of these effects are significant. This indicates that effective integration between Supply Chain Management strategies and Open Innovation can improve organizational performance. TMKV has a significant positive impact on KSP, KSP also has a significant positive impact on IOI, IOI has a significant positive impact on OP, and KSP mediated by IOI is proven to have a significant positive effect in supporting OP, while OOI mediation is not proven. This study is not intended to generalize a theory due to the limitations in sample size, industry, and geographical area.